Temperature effects on photosynthesis in gametophytic and sporophytic stages of the freshwater red alga Sirodotia delicatula (Rhodophyta, Batrachospermales) under a global warming perspective - Vilas Boas, Lucas K. [UNESP]; Oliveira, Régis de C. [UNESP]; Necchi, Orlando [UNESP]; Branco, Ciro C. Z. [UNESP] (Wiley, 2018)
The increase in Earth's global mean temperature due to human influence has become a major concern, with ecological consequences already being reported around the world. In tropical streams, benthic red algae belonging to the order Batrachospermales contribute to a large fraction of the community energy input and play an important role in sustaining autotrophic food webs. The Batrachospermales also have a unique life history, with heteromorphic life stages (gametophytes and sporophytes) occurring seasonally and with distinct ecological roles. Through “in vivo” chlorophyll fluorescence and dissolved oxygen evolution techniques, we evaluated the effects of projected temperature increases of two future scenarios (RCP 4.5 and RCP 8.5) on the photosynthetic response of Sirodotia delicatula gametophytes and sporophytes. In general, both chlorophyll fluorescence and dissolved oxygen showed that the RCP 8.5 scenario could severely jeopardize the photosynthetic performance of the sporophytes during the summer while also providing a stressful physiological situation to the gametophytes. Due to the crucial role of sporophytes in the development of this species, results indicate that this predicted scenario could affect this species. Given the position of these organisms at the base of the food web in tropical lotic environments, especially in shaded low-order streams, such impact could generate unforeseen cascade effects on higher trophic levels.
Keywords: Chantransia; climate change; Intergovernmental Panel on Climate Change; lotic ecosystem; macroalgae; stream; tropical